Orientation control during 2D-3D composite preforming - Gibbs, Albert Oswald (2023)
Non-crimp fabrics (NCFs) are employed in composite structures as an alternative to woven fabrics when there is a requirement for improved tensile strength and modulus. To exploit NCF properties, components are designed with optimised fibre directions that reinforce the predicted load paths. 2D to 3D composite forming is a manufacturing method that has been developed for automation, to improve the labour economy of components and reduce per unit costs. Currently it is difficult to maintain accurate fibre orientation control due to the constraints of the 2D pre-form and the lack of interaction with the fabric during its transition from a 2D to a 3D form.